Optical spectra in helium plasma generated by nuclear fission fragments - Kunakov, S. K.; Son, E. E.; Bolatov, Zh.; Kaster, M. (International Journal of Mathematics and Physics, 2015)
мSpectral study of optical radiation plasma formed by the products of uclear reactions has some definite feature (unlike many other works on the rradiation of materials in the reactor) that experimental measurements should be carried out in a reactor at power. Problems associated with such types of expe-rimental works are to provide biological protection with inimal loss of light emission and the difficulties of registration of the spectrum in the active zone of nuclear reactor. The first problem is solvable by choosing a specific design of the experimental setup; the second allows us to solve the photoelectric me-thod of recording optical radiation, particularly using a photon counting technique.